Measuring the Effectiveness of Marketing Communication Using AISAS ARCAS Model (Case Study: Bagoes Bag by PT. Greeneration Indonesia) - Amaly, Laressa; Hudrasyah, Herry (Journal of Business and Management, 2012)
Purpose: The paper aims to measure the marketing communication performance and effectiveness for BaGoes in order to improve the promotion, product aspects that affecting the promotion, strehgthen or rebuild product image. Design/methodology/approach: This paper is based on AISAS ARCAS model framework for measuring marketing communication performance, by means it is also used to evaluate the promotion/ads and product aspect that affecting the promotion. Questionnaire, in depth interview and observations are used for research approach. Number sample of 206 respondents of BaGoes target market in Bandung was collected through convenience sampling. Factor analysis and multiple regression analysis were used to test the proposed model. Interview and obeservations functioned as crosscheck tools for quantitative analysis also constructing deeper research and finding. Findings: The result conveys that current marketing communications is not effective. Variable Attention and Interest are the important fundamental basis for the purchase action. In addition, variable Sustain also influence purchases, Research limitations/implication: BaGoes is the only product that used as an object of the research and only conducted in Bandung. For future research, it is suggested to use structural equation modeling (SEM) in assessing the interrelationship of the variable in the proposed model. Practical implication: In order to make the product sustainable, the directors should develop strategy and focus on consumer perception by improving variable Attention, Interest, and Sustain. Originality/value: This paper contributes in marketing communication effectiveness measurement using AISAS ARCAS Model. Keywords: Marketing Communication, AISAS ARCAS Model, Advertising, Promotion Category: Marketing